Rifles for Watie - Keith, Harold, 1903-1998. (New York : HarperTrophy, 1957)
The story of Jeff Bussey, a farm boy living in 1861, who joins the Union army and goes on an important mission to discover how Stand Watie and his Confederate Cherokee Rebels are receiving repeating rifles from northern manufacturers
Linn County, Kansas, 1861 -- Bushwhackers -- Fort Leavenworth -- Captain Asa Clardy -- Furlough -- March -- Battle of Wilson's Creek -- Hard Lessons -- Light Bread and Apple Butter -- Foraging in the Cherokee County -- Lucy Washbourne -- Battle of Prairie Grove -- Expedition to Van Buren -- The Cow Lot -- Fate of the Brandts -- The Name on the Watch -- The Ride of Noah Babbitt -- Sunday --Wrong Side of the River -- The Jackmans -- Boggy Depot -- Pheasant Bluff -- The Redbud Tree -- Flight -- Linn County, Kansas, 1861
"A Harper Keypoint book."
"Trophy Newbery"--Spine
Originally published 1957
Keywords: Watie, Stand, -- Fiction; United States -- History -- Civil War, 1861-1865 -- Fiction